Analisis Lintasan Kritis Kegiatan Impor Material dan Peralatan Proyek PLTU Lontar 315 MW Tangerang - Hendro Kuntohadi; Garendra Garendra; Cecep Budiman (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2019)
The research was conducted at PT Satyamitra Surya Perkasa (PT.SSP) in Jakarta. The purpose of the research is to find out the flow of imported goods procurement in PT. SSP in 2017. This is an action research where the researchers can describe, interpret, and define a situation by changing…The data used in this study was qualitative data. The data was taken by interviewing and doing library research. The scheduler with exact time work duration and high probability for success was resulted from the implementation of CPM PERT critical flow and bar chart scheduling. This study analyzes the data from the process of procuring imported goods from the initial project request to the fulfillment of the material procurement head office which will eventually be used for project needs. The critical trajectory analysis using the PERT and Network Diagram CPM methods can indicate that the procurement of imported goods that have been analyzed normally in the day is 65 days after the assessment is conducted both in terms of time and expenditure of company funds for goods demand, goods ordering, customs clearance, shipping loading and unloading document and trucking, the time can be shortened to 45 days, and has a major impact on the development needs of the 2017 Lontar PLTU project.